2016
DOI: 10.1053/j.gastro.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Bleeding Recurrence and Cardiovascular Events With Continued Aspirin Use After Lower Gastrointestinal Hemorrhage

Abstract: Among aspirin users with a history of lower GI bleeding, continuation of aspirin is associated with an increased risk of recurrent lower GI bleeding, but reduced risk of serious cardiovascular events and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 22 publications
6
58
0
Order By: Relevance
“…A cohort study by Chan et al compared patients who continued long-term aspirin after admission with LGIB, versus those who discontinued it. The latter group had fewer rebleeding events, but significantly more cardiovascular events and deaths 104. This is in keeping with the cohort study by Oakland et al on a short interruption of antiplatelet therapy 112…”
Section: Drug Therapy Considerations In Acute Lgibsupporting
confidence: 85%
See 1 more Smart Citation
“…A cohort study by Chan et al compared patients who continued long-term aspirin after admission with LGIB, versus those who discontinued it. The latter group had fewer rebleeding events, but significantly more cardiovascular events and deaths 104. This is in keeping with the cohort study by Oakland et al on a short interruption of antiplatelet therapy 112…”
Section: Drug Therapy Considerations In Acute Lgibsupporting
confidence: 85%
“…Predominantly the anticoagulant effect of direct oral anticoagulants (DOACs) is managed by simply withholding this medication. No drug can easily reverse the platelet dysfunction seen with antiplatelets, and these agents are mostly withheld in the acute setting of LGIB,6 despite evidence of poorer cardiovascular outcomes in the long term 104

We recommend interrupting warfarin therapy at presentation ( weak recommendation, low quality evidence ).

…”
Section: Drug Therapy Considerations In Acute Lgibmentioning
confidence: 99%
“…Decisions regarding withholding antiplatelets in patients presenting with LGIB are difficult since continued antiplatelet use is associated with rebleeding,27 but withholding them may lead to increased cardiovascular morbidity 28. Guidelines recommend that patients receiving aspirin for secondary prevention of high-risk cardiovascular disease should not have this drug stopped 6.…”
Section: Discussionmentioning
confidence: 99%
“…Agreement rate: 88% Explanation Post-admission management is essential because of the association between discontinuation of antithrombogenic drugs and risk of thromboembolism or subsequent death [46][47][48][49][50][51]. A common recommendation among preexisting guidelines [34,[52][53][54][55][56][57] is that drugs should be discontinued after dialogue and in close collaboration with experts in different fields such as hematologists, cardiologists, neurologists, and gastroenterologists.…”
Section: Quality Of Evidence: C Strength Of Recommendation: Probably mentioning
confidence: 99%
“…Retrospective cohort studies in patients with aspirinassociated acute lower GIB [46,49,51] have shown that the discontinuation of aspirin was associated with a significantly lower rate of rebleeding but also a significantly higher number of adverse cardiovascular events compared with the continuation and re-administration of aspirin [46]. A randomized controlled study of patients with aspirin-associated upper GI bleeding has also demonstrated increased risks of cardiovascular events and mortality after discontinuation of aspirin, suggesting the advantages of resuming aspirin early [51].…”
Section: Cq24: Should Anticoagulant Therapy Be Resumed After Temporarmentioning
confidence: 99%